Elective Stoma Reversal Has a Higher Incidence of Postoperative Clostridium Difficile Infection Compared With Elective Colectomy: An Analysis Using the American College of Surgeons National Surgical Quality Improvement Program and Targeted Colectomy Databases. Issue 5 (May 2018) - Skancke, Matthew; Vaziri, Khashayar; Umapathi, Bindu; Amdur, Richard; Radomski, Michal; Obias, Vincent
Abstract : BACKGROUND: Clostridium difficile infection is caused by the proliferation of a gram-positive anaerobic bacteria after medical or surgical intervention and can result in toxic complications, emergent surgery, and death. OBJECTIVE: This analysis evaluates the incidence of C difficile infection in elective restoration of intestinal continuity compared with elective colon resection. DESIGN: This was a retrospective database review of the 2015 American College of Surgeons National Surgical Quality Improvement Project and targeted colectomy database. SETTINGS: The intervention cohort was defined as the primary Current Procedural Terminology codes for ileostomy/colostomy reversal (44227, 44620, 44625, and 44626) and International Classification of Diseases codes for ileostomy/colostomy status (VV44.2, VV44.3, VV55.2, VV55.3, Z93.2, Z93.3, Z43.3, and Z43.2). PATIENTS: A total of 2235 patients underwent elective stoma reversal compared with 10403 patients who underwent elective colon resection. INTERVENTION: Multivariate regression modeling of the impact of stoma reversal on postoperative C difficile infection risk was used as the study intervention. MAIN OUTCOME MEASURES: The incidence of C difficile infection in the 30 days after surgery was measured. RESULTS: The incidence of C difficile infection in the 30-day postoperative period was significantly higher (3.04% vs 1.25%; p < 0.001) in patients undergoing stoma reversal. After controlling for differences in cohorts, regression analysis suggested that stoma reversal (OR = 2.701 (95% CI, 1.966–3.711); p < 0.001), smoking (OR = 1.520 (95% CI, 1.063–2.174); p = 0.022), steroids (OR = 1.677 (95% CI, 1.005–2.779); p = 0.048), and disseminated cancer (OR = 2.312 (95% CI, 1.437–3.719); p = 0.001) were associated with C difficile infection incidence in the 30-day postoperative period. LIMITATIONS: The study was limited because it was a retrospective database review with observational bias. CONCLUSIONS: Patients who undergo elective stoma reversal have a higher incidence of postoperative C difficile infection compared with patients who undergo an elective colectomy. Given the impact of postoperative C difficile infection, a heightened sense of suspicion should be given to symptomatic patients after stoma reversal. See atVideo Abstract athttp://links.lww.com/DCR/A553 .